Mycotoxin binders: An option for safer milk in Kenya? - Mutua, Florence K.; Lindahl, Johanna F.; Grace, Delia (International Livestock Research Institute, 2019)
Aflatoxins are a recurring problem in Kenya, and levels exceeding the recommended limits have been documented in both human food as well as animal feeds. Consumption of products contaminated with aflatoxins can have serious health effects, including liver cancer from chronic exposure. Aflatoxins also cause problems in livestock production, with animals producing less, and there are also concerns about aflatoxins in the animal products, especially dairy products. Aflatoxin M1 (AFM1) is found in milk from cows fed on diets contaminated with aflatoxin B1 (AFB1). In order to protect milk from getting contaminated, milking cows should not be fed too high levels of aflatoxins. Binders are mixed with feed, and when ingested, sequester the toxins in the gastrointestinal tract of the animal. Bound toxins are eliminated in faeces and their bioavailability is reduced. As a result of this, the animal is protected from possible negative effects and safer milk is produced. Objective: We provide a discussion on the potential of mycotoxin binders in addressing the problem of aflatoxins in smallholder dairy systems of Kenya. Methodology: Our discussion is based on what is available in literature, visits to selected agrovet and animal feed outlets, and lessons learnt while implementing a pilot to assess binder use in the field. Results: A summary of mycotoxin binder types available in Kenya is given and a highlight of constraints to their current use is provided. We also give suggestions on what can be done to promote their use by smallholders across the country. Conclusions: Mycotoxin binders are an option for reducing aflatoxin concentration in cow milk. Sustainable marketing channels need to be explored as more research is done to characterize their effectiveness in smallholder systems.